Surveillance Duplex Ultrasonography of Stent Grafts for Popliteal Aneurysms. (May 2016) - Pineda, Danielle M.; Troutman, Douglas A.; Dougherty, Matthew J.; Calligaro, Keith D.
Objective: Stent grafts, also known as covered stents, have become an increasingly acceptable treatment for popliteal artery aneurysms. However, endovascular exclusion confers lower primary patency compared to traditional open bypass and exclusion. The purpose of this study was to evaluate whether duplex ultrasonography (DU) can reliably diagnose failing stent grafts placed for popliteal artery aneurysms prior to occlusion. Methods: Between June 5, 2007, and March 11, 2014, 21 stent grafts (Viabahn; Gore, Flagstaff, Arizona) were placed in 19 patients for popliteal artery aneurysms. All patients had at least 1 follow-up duplex scan postoperatively. Mean follow-up was 28.9 months (9-93 months). Postoperative DU surveillance was performed in our Intersocietal Accreditation Commission noninvasive vascular laboratory at 1 week postprocedure and every 6 months thereafter. Duplex ultrasonography measured peak systolic velocities (PSVs) and ratio of adjacent PSVs (Vr) every 5 cm within the stent graft and adjacent arteries. Results: We retrospectively classified the following factors as "abnormal DU findings": focal PSV > 300 cm/s, uniform PSVs < 50 cm/s throughout the graft, and Vr > 3.0. These DU criteria were derived from laboratory-specific data that we previously published on failing stent grafts placed for lower extremity occlusive disease. Four of the 21 stent grafts presented with symptomatic graft thrombosis within 6 months of a normal DU. Three of these 4 patients presented with rest pain and underwent thrombectomy (2) or vein bypass (1), and 1 elected for nonintervention for claudication. Conclusion: Our results suggest that surveillance DU using criteria established for grafts placed for occlusive disease may not be useful for predicting stent graft failure in popliteal artery aneurysms.